Penerapan Asas In Flagrante Delicto Dalam Menyelesaikan Perceraian Dengan Alasan Zina: Pandangan Hakim Pa Stabat - Irma Khairani; Syahrul Affan; Diyan Yusri (Peduli Riset dan Pengabdian Masyarakat, 2025)
This study is entitled The Application of the In Flagrante Delicto Principle in Divorce Cases Based on Adultery at the Stabat Religious Court. This research employs a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation. The findings indicate that the in flagrante delicto principle is not positioned as a normative legal basis in divorce cases but is understood as a legal fact assessed within the framework of civil procedural evidence. Judges do not require proof of being caught in the act to establish adultery, as such a requirement is not explicitly regulated in Law Number 1 of 1974, Government Regulation Number 9 of 1975, or the Compilation of Islamic Law. Proof of adultery is conducted based on Article 164 of the HIR and Article 284 of the RBg through a cumulative and comprehensive evaluation of evidence. The perspective of judges at the Stabat Religious Court shows that proving adultery in divorce cases is not intended to establish a criminal offense, but rather to assess whether the marital relationship can still be maintained or has lost its harmonious foundation. Judicial considerations emphasize the impact of the act on the integrity of the household rather than direct proof of adultery, while upholding the principles of prudence, substantive justice, and protection of the parties’ dignity. This approach reflects the objectives of law as proposed by Gustav Radbruch in balancing legal certainty and justice, aligns with Satjipto Rahardjo’s progressive legal thought, and corresponds to the principles of maqāṣid al-sharī‘ah in safeguarding honor and lineage. Juridical obstacles arise due to the absence of explicit regulations governing this principle in civil procedural law and religious court regulations. Practical obstacles include the difficulty of proving adultery, the dominance of indirect and electronic evidence, and ethical and moral dilemmas related to the dignity of the parties. To address these challenges, judges apply principles of prudence, careful assessment, and moral courage to avoid imposi